Environment-friendly basketball leather and preparation method thereof

By adopting a sandwich structure with composite PU surface layer and modified thermally expanded microspheres in the basketball leather, the existing environmentally friendly basketball leather has been solved, and the wear resistance and impact resistance is achieved is achieved, which extends the service life and improves sports safety.

CN119900180APending Publication Date: 2025-04-29SUZHOU RUIGAO QIHANG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510160896.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing environmentally friendly basketball leather has shortcomings in improving wear resistance and impact resistance, which affects service life and sports safety.

Method used

A sandwich structure with a composite PU surface layer, including a first PU surface layer, a fiber reinforced layer and a second PU surface layer, is used to form a multi-layer structure with good wear resistance and impact resistance in combination with modified thermally expanded microspheres and carbon nanopowder.

Benefits of technology

It significantly improves the wear resistance and impact resistance of the basketball leather, extends the service life, improves sports safety, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005271003740000061
    Figure BDA0005271003740000061
  • Figure BDA0005271003740000081
    Figure BDA0005271003740000081
  • Figure BDA0005271003740000091
    Figure BDA0005271003740000091
Patent Text Reader

Abstract

The invention relates to the technical field of synthetic leather, and particularly discloses environment-friendly basketball leather and a preparation method thereof. The environment-friendly basketball leather comprises a base cloth layer, a composite PU surface layer and a surface coating layer which are sequentially attached, the composite PU surface layer comprises a first PU surface layer, a fiber reinforcement layer and a second PU surface layer which are sequentially attached, and the side, away from the fiber reinforcement layer, of the first PU surface layer is attached to the base cloth layer; the first PU surface layer is prepared from the following raw materials: thermoplastic polyurethane, a thickening agent, a flatting agent, a cross-linking agent and a foam stabilizer; the second PU surface layer is prepared from the following raw materials: waterborne polyurethane, modified thermal expansion microspheres, a flatting agent, a cross-linking agent and a defoaming agent. The preparation raw materials of the environment-friendly basketball leather are environment-friendly and meet the requirements of sustainable development, and the finished product has excellent wear resistance and strike resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of synthetic leather, and more specifically, to an environmentally friendly basketball leather and a preparation method thereof. Background Art

[0002] Synthetic leather is a plastic product that simulates the composition and structure of natural leather and can be used as a substitute for it. Both the front and back sides are very similar to leather and have a certain degree of breathability. It is closer to natural leather than ordinary artificial leather and is widely used in the production of shoes, bags, balls, yoga mats, floor mats and other fields.

[0003] Basketball is a common sport ball. Currently, there are real leather and simulated leather. The most widely used is the ball leather made of polyvinyl chloride (PVC) and polyurethane (PU). These materials may produce harmful substances during the production process, such as sulfides, chlorides, phthalates and DMF wastewater discharge, etc. The existing primary recycling methods are difficult to completely recycle these harmful substances, and it is difficult to meet environmental protection requirements, which poses a potential risk to the environment and human health. Therefore, the development of an environmentally friendly basketball leather is an inevitable market demand.

[0004] In view of the above-mentioned related technologies, the inventors found that the environmentally friendly basketball leather under the existing technology still has deficiencies in improving wear resistance and impact resistance. The wear resistance of basketball leather is directly related to the service life of the basketball and the safety of sports. Poor wear resistance may cause the surface coating to fall off quickly, affecting the user experience and increasing the frequency of replacement, thereby causing a waste of resources. The impact resistance of basketball leather is also crucial to ensure stability during exercise and the safety of players. Summary of the invention

[0005] In order to improve the wear resistance and impact resistance of environmentally friendly basketball leather and enhance the durability of environmentally friendly basketball leather, the present application provides an environmentally friendly basketball leather and a preparation method thereof.

[0006] In the first aspect, the present application provides an environmentally friendly basketball leather, which adopts the following technical solution: An environmentally friendly basketball leather, comprising a base fabric layer, a composite PU surface layer and a surface finishing layer laminated in sequence, wherein the composite PU surface layer comprises a first PU surface layer, a fiber reinforcement layer and a second PU surface layer laminated in sequence, and the first PU surface layer is laminated to the base fabric layer on a side away from the fiber reinforcement layer; In parts by weight, the raw materials of the first PU surface layer include 15-25 parts of thermoplastic polyurethane, 0.2-0.5 parts of thickener, 0.01-0.05 parts of first leveling agent, 0.5-1 parts of first cross-linking agent and 0.5-1 parts of foam stabilizer; The raw materials of the second PU surface layer include 30-45 parts of the first waterborne polyurethane, 3-7 parts of modified thermal expansion microspheres, 0.1-0.5 parts of The second leveling agent, 1.2-1.5 parts of the second cross-linking agent and 0.1-0.3 parts of the defoaming agent.

[0007] By adopting the above technical solution, the composite PU surface layer is formed by laminating the first PU surface layer, the fiber reinforcement layer and the second PU surface layer in sequence to form a sandwich structure. The first PU surface layer uses thermoplastic polyurethane, which has good wear resistance and flexibility. It is laminated with the base fabric layer, which can effectively enhance the overall support of the basketball leather and form a more solid support matrix with good resilience; the second PU surface layer uses water-based polyurethane, which has good wear resistance, water resistance and bonding properties. It is laminated with the surface coating layer to form a waterproof and wear-resistant protective layer. The fiber reinforcement layer in the middle further enhances the wear resistance and impact resistance of the basketball leather.

[0008] As a filler for the second PU surface layer, the addition of modified heat-expandable microspheres can effectively improve the elasticity and impact resistance of basketball leather, which is especially important when basketball frequently hits the ground, and can significantly improve the durability of basketball leather.

[0009] The modified heat-expandable microspheres have a unique shell-sheath structure. The shell and core material can expand under certain conditions, and a certain elastic layer can be formed after expansion, which increases the elasticity and toughness of the basketball leather, making it better able to resist deformation and damage when facing blows. When subjected to external forces, this structure can absorb and disperse part of the impact energy and convert it into deformation energy or heat energy of the microspheres, thereby reducing the direct impact of the impact on the basketball leather matrix. The expansion and deformation process of the microspheres is accompanied by energy dissipation, which helps to further reduce the stress level of the basketball leather when it is hit and improve the impact resistance of the basketball leather.

[0010] In addition, the modified heat-expandable microspheres can fill the tiny pores and defects inside the basketball leather, increase the density and tightness of the basketball leather, and reduce the stress concentration caused by material unevenness or defects. This filling effect helps to improve the overall strength and wear resistance of the basketball leather.

[0011] Optionally, the raw materials of the modified heat-expandable microspheres include, by weight, 15-25 parts of cyano-containing olefin monomers, 5-10 parts of double-bond-containing ester monomers, 2-7 parts of carbon nanopowder, 0.2-0.8 parts of initiators and 5-10 parts of low-boiling-point alkanes, and also include 1-1.5 parts of sodium dodecyl sulfate, 0.1-0.3 parts of polyvinyl pyrrolidone, 0.1-0.3 parts of sodium nitrite and 10-15 parts of sodium chloride.

[0012] By adopting the above technical solution, the carbon nanopowder has excellent wear resistance, can maintain good stability during friction, and when combined with other components in basketball leather, can form a wear-resistant composite layer, effectively resisting external wear and extending the service life of basketball leather. Due to the nanoscale size effect of carbon nanopowder, it can be better dispersed during the preparation of modified thermal expansion microspheres, effectively preventing agglomeration inside the microspheres. When the modified thermal expansion microspheres are combined with other components of basketball leather, the modified thermal expansion microspheres can also be more evenly dispersed, thereby improving the uniformity and stability of the microspheres.

[0013] In addition, the combination of carbon nanopowder and thermal expansion microspheres can form a more complex energy absorption and dissipation mechanism. When the basketball leather is hit, the carbon nanopowder in the microspheres can absorb and disperse part of the impact energy, and at the same time work synergistically with the expansion process of the microspheres to further reduce the stress level of the basketball leather and improve the impact resistance of the basketball leather.

[0014] Optionally, the cyano group-containing olefin monomer is selected from any one of acrylonitrile or crotononitrile; the double bond-containing ester monomer is methyl methacrylate, butyl acrylate and vinyl acetate in a mass ratio of 1:(2-6):(1-5); the initiator is azobisisobutyronitrile; and the low-boiling alkane is selected from any one of isopentane or n-octane.

[0015] Optionally, the method for preparing the modified heat-expandable microspheres comprises the following steps: Sodium lauryl sulfate, polyvinyl alcohol, sodium nitrite and sodium chloride are mixed and added into deionized water at a solid-liquid ratio of 1:(9-11) to form an aqueous phase; The cyano-containing olefin monomer, the double-bond-containing ester monomer, the carbon nanopowder, azobisisobutyronitrile and the low-boiling-point alkane are mixed and stirred uniformly to obtain an oil phase; The oil phase is added to the water phase, stirred at a speed of 8000-9000 rpm for 3-5 minutes to disperse, and then pressurized under a nitrogen atmosphere, reacted at 50-80° C. for 18-20 hours, then reduced in pressure, cooled to room temperature, centrifuged, dried, and sieved to obtain the product.

[0016] By adopting the above technical scheme, through specific mixing, dispersion and polymerization reactions, heat-expandable microspheres with good dispersion properties can be formed and evenly dispersed in the second PU surface layer of the basketball leather, playing an effective reinforcement role.

[0017] Optionally, the fiber reinforcement layer comprises nylon, polylactic acid fiber and carbon fiber in a mass ratio of (5-7):(2-4):(1-3).

[0018] By adopting the above technical solution, nylon, polylactic acid fiber and carbon fiber themselves have good wear resistance. Polylactic acid fiber itself is a bio-based material with good environmental performance. The mixture of the three as a fiber reinforcement layer can significantly improve the strength and wear resistance of basketball leather.

[0019] Optionally, the raw materials of the surface finishing layer include 5-10 parts of a second waterborne polyurethane, 5-10 parts of rosin resin and 20-30 parts of butanone.

[0020] By adopting the above technical scheme, a surface coating layer with good anti-slip and wear resistance is prepared by mixing water-based polyurethane resin, rosin resin and butanone. When applied to the surface of synthetic leather for balls, the performance of the balls can be effectively improved.

[0021] Optionally, the base fabric layer is made of polylactic acid non-woven fabric.

[0022] By adopting the above technical solution, the non-woven fabric is made of fine fibers interwoven and bonded with each other, and has a rich microporous structure on the surface and inside, forming a three-dimensional structure. This structure gives the non-woven fabric good toughness and ductility, and enhances the interaction between the fibers. When the non-woven fabric is used as the base fabric layer and combined with polymer materials such as water-based polyurethane (PU) of synthetic leather, a composite multi-layer structure is formed. This structure enables the synthetic leather to act as a supporting layer when subjected to external forces, effectively dispersing and resisting the impact of external forces, thereby improving the wear resistance and impact resistance of the basketball leather.

[0023] Polylactic acid non-woven fabric as the base fabric layer not only improves the wear resistance and impact resistance of basketball leather, but also has environmental protection properties, which is in line with the concept of sustainable development.

[0024] Optionally, the thickness of the first PU surface layer is 0.26-0.3 mm, the thickness of the fiber reinforced layer is 0.1-0.13 mm, and the thickness of the second PU surface layer is 0.42-0.47 mm.

[0025] By adopting the above technical solution, the thickness of each layer in the composite PU surface layer can be accurately controlled, so that the performance of the composite PU surface layer can be optimized.

[0026] In a second aspect, the present application provides a method for preparing an environmentally friendly basketball leather, using the following technical solution: A method for preparing an environmentally friendly basketball leather comprises the following steps: S1: mixing corresponding masses of thermoplastic polyurethane, thickener, first leveling agent, first crosslinking agent and foam stabilizer to prepare slurry A; mixing corresponding masses of first waterborne polyurethane, modified thermal expansion microspheres, second leveling agent, second crosslinking agent and defoamer to prepare slurry B; S2: Slurry A is coated on the base fabric layer to prepare a first PU surface layer, and then the fiber reinforcement layer is placed on the side of the slurry A coating layer away from the base fabric layer, and then rolled and dried to form a semi-cured base fabric A; S3: coating the slurry B on the side of the fiber reinforcement layer away from the base fabric layer in the semi-cured base layer A to prepare a second PU surface layer, and drying to obtain the semi-cured base fabric B; S4: embossing the semi-cured base fabric B; S5: The second water-based polyurethane, rosin resin and butanone are mixed according to mass to prepare a surface coating liquid, which is applied to one side of the printed surface of the semi-cured base fabric B to prepare a surface coating layer, which is then dried.

[0027] By adopting the above technical scheme, the method uses environmentally friendly materials such as thermoplastic polyurethane and water-based polyurethane. These materials have little impact on the environment during production and use. When preparing the surface coating layer, environmentally friendly solvents such as butanone are used. Compared with traditional solvents, they have lower volatility and less harm to the environment and operators, which meets modern environmental protection requirements.

[0028] Combining the base fabric layer, composite PU surface layer and surface coating layer to form a multi-layer structure can significantly improve the structural strength and durability of basketball leather. The addition of fiber reinforcement layer further enhances the strength and wear resistance of basketball leather, enabling it to withstand greater external forces and impacts.

[0029] Precisely controlling the coating thickness and drying conditions of each layer of raw materials ensures uniform distribution of each layer of materials and optimized performance. The process is simple and convenient for industrial-scale production.

[0030] Optionally, the method for preparing the fiber reinforced layer comprises the following steps: Nylon, polylactic acid fiber and carbon fiber are cut into short fibers respectively and then mixed evenly, opened and blended with cotton; the blended fibers are combed into a fiber web and then needle-punched to obtain the fiber web.

[0031] By adopting the above technical solution, nylon, polylactic acid fiber and carbon fiber are made into non-woven fabrics by needle punching. Since the non-woven fabric is formed by interweaving specific and random fibers to form a specific network structure, this structure can enhance the interaction force between fibers, effectively resist tearing, and improve the mechanical properties of basketball leather; at the same time, the porous structure and fiber interweaving of the non-woven fabric can absorb and disperse the energy generated by the impact, reduce the direct impact of energy on the basketball leather, and thus improve the impact resistance of the basketball leather.

[0032] In summary, this application has the following beneficial effects: 1. Since the composite PU surface layer of the present application is a sandwich structure formed by sequentially bonding a first PU surface layer, a fiber reinforcement layer, and a second PU surface layer, it can effectively improve the overall supporting strength of the basketball leather base fabric layer, forming a more solid supporting matrix with good resilience, which can enhance the wear resistance and impact resistance of the basketball leather and extend the durability of the basketball leather.

[0033] 2. Modified heat-expandable microspheres are added to the second PU surface layer of the present application. The unique shell-sheath structure enables the basketball leather to better resist deformation when facing impact, and absorb and disperse part of the impact capacity, effectively reducing the impact of the impact force on the basketball leather, and effectively improving the impact resistance of the basketball leather.

[0034] 3. The method of the present application, by adopting environmentally friendly materials such as thermoplastic polyurethane and water-based polyurethane, has little impact on the environment during production and use, meets modern environmental protection requirements, and helps promote sustainable development. DETAILED DESCRIPTION

[0035] The following examples further illustrate the present application in detail.

[0036] raw material Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples in this application are all commercially available products, specifically: Methyl methacrylate, selected from Asahi Kasei PM120N; Butyl acrylate, selected from DuPont 34035AC; Vinyl acetate, selected from Mantanghong New Material HG145; Carbon nanopowder, selected from Pioneer Nano XFN34 7440-44-0; Thermoplastic polyurethane, selected from Wanhua WHT-1172IC; Thickener, selected from Evotexxal WUF; The first leveling agent and the second leveling agent are selected from Evoprtrea DT; The first crosslinker and the second crosslinker are selected from Stahl XR-5588; Foam stabilizer, selected from Juepai PN-01; Defoamer, selected from Stahl DF-2459; The first waterborne polyurethane is selected from Huada DG-6115; A second waterborne polyurethane selected from Stahl RU-92-213; Rosin resin, selected from Xingli New Material 424; Carbon fiber is selected from Kejing carbon fiber KJF1000.

[0037] Preparation Example 1.1-1.5 of Modified Thermally Expandable Microspheres Preparation Example 1.1 The modified heat-expandable microspheres, the raw materials and amounts are shown in Table 1, wherein the cyano-containing olefin monomer is crotononitrile, the double-bond-containing ester monomer is methyl methacrylate, butyl acrylate and vinyl acetate in a mass ratio of 1:2:1, the initiator is azobisisobutyronitrile, and the low-boiling alkane is isopentane.

[0038] Table 1 The preparation method of the modified heat-expandable microspheres comprises the following steps: S1: mixing sodium lauryl sulfate, polyvinyl alcohol, sodium nitrite and sodium chloride, and adding them into deionized water at a solid-liquid ratio of 1:9 to form an aqueous phase; S2: mixing and stirring the cyano group-containing olefin monomer, the double bond-containing ester monomer, the carbon nanopowder, azobisisobutyronitrile and the low-boiling-point alkane to obtain an oil phase; S3: Add the oil phase to the water phase, stir for 4 min at a high shear disperser at a speed of 9000 rpm to obtain a dispersion, add the dispersion into a reactor with pressure and stirring functions, and then pressurize to 1 MPa under a nitrogen atmosphere, react at 60°C for 20 h, then reduce the pressure, cool to room temperature, centrifuge, dry, and sieve to obtain the dispersion.

[0039] Preparation Example 1.2 The modified heat-expandable microspheres are different from those in Preparation Example 1.1 in that the raw materials and their amounts are as shown in Table 1, wherein the cyano-containing olefin monomer is acrylonitrile, the double-bond-containing ester monomer is methyl methacrylate, butyl acrylate and vinyl acetate in a mass ratio of 1:4:3, and the low-boiling-point alkane is n-octane; The preparation method of the modified heat-expandable microspheres comprises the following steps: S1: mixing sodium lauryl sulfate, polyvinyl alcohol, sodium nitrite and sodium chloride, and adding them into deionized water at a solid-liquid ratio of 1:10 to form an aqueous phase; S2: mixing and stirring the cyano group-containing olefin monomer, the double bond-containing ester monomer, the carbon nanopowder, azobisisobutyronitrile and the low-boiling-point alkane to obtain an oil phase; S3: Add the oil phase to the water phase, stir for 5 minutes at a high shear disperser at a speed of 8000 rpm to obtain a dispersion, add the dispersion into a reactor with pressure and stirring functions, and then pressurize to 1 MPa under a nitrogen atmosphere, react at 50°C for 20 hours, then reduce the pressure, cool to room temperature, centrifuge, dry, and sieve to obtain the dispersion.

[0040] Preparation Example 1.3 The modified heat-expandable microspheres are different from those in Preparation Example 1.1 in that the raw materials and amounts are as shown in Table 1, and the double-bond-containing ester monomers are methyl methacrylate, butyl acrylate and vinyl acetate in a mass ratio of 1:3:5; The preparation method of the modified heat-expandable microspheres comprises the following steps: S1: mixing sodium lauryl sulfate, polyvinyl alcohol, sodium nitrite and sodium chloride, and adding them into deionized water at a solid-liquid ratio of 1:11 to form an aqueous phase; S2: mixing and stirring the cyano group-containing olefin monomer, the double bond-containing ester monomer, the carbon nanopowder, azobisisobutyronitrile and the low-boiling-point alkane to obtain an oil phase; S3: Add the oil phase to the water phase, stir for 3 minutes at a high shear disperser at a speed of 9000 rpm to obtain a dispersion, add the dispersion into a reactor with pressure and stirring functions, pressurize to 1 MPa under a nitrogen atmosphere, react at 80°C for 18 hours, then reduce the pressure, cool to room temperature, centrifuge, dry and sieve to obtain the dispersion.

[0041] Preparation Example 1.4 The modified heat-expandable microspheres are different from those in Preparation Example 1.1 in that the raw materials and amounts are as shown in Table 1, the double-bond-containing ester monomers are methyl methacrylate, butyl acrylate and vinyl acetate in a mass ratio of 1:6:2, and the other steps are the same as those in Preparation Example 1.1.

[0042] Preparation Example 1.5 The modified heat-expandable microspheres are different from those in Preparation Example 1.1 in that no carbon nanopowder is added to the raw materials, and the other steps are the same as those in Preparation Example 1.1.

[0043] Preparation Examples 2.1-2.4 of Fiber Reinforced Layers Preparation Example 2.1 The fiber-reinforced layer comprises nylon, polylactic acid fiber and carbon fiber in a mass ratio of 5:4:3, and the preparation method thereof comprises the following steps: S1: nylon, polylactic acid fiber and carbon fiber are cut into short fibers respectively, and the three short fibers are opened and then placed in a cotton blending machine for blending; S2: The mixed fibers are combed into a fiber web in a carding machine, and then the fiber web is put into a needle punching machine for needle punching, so that the thickness of the fiber reinforcement layer is 0.1 mm.

[0044] Preparation Example 2.2 The fiber-reinforced layer comprises nylon, polylactic acid fiber and carbon fiber in a mass ratio of 6:3:1, and the preparation method thereof comprises the following steps: S1: nylon, polylactic acid fiber and carbon fiber are cut into short fibers respectively, and the three short fibers are opened and then placed in a cotton blending machine for blending; S2: The mixed fibers are combed into a fiber web in a carding machine, and then the fiber web is put into a needle punching machine for needle punching, so that the thickness of the fiber reinforcement layer is 0.13 mm.

[0045] Preparation Example 2.3 The fiber-reinforced layer comprises nylon, polylactic acid fiber and carbon fiber in a mass ratio of 7:2:2, and the preparation method thereof comprises the following steps: S1: nylon, polylactic acid fiber and carbon fiber are cut into short fibers respectively, and the three short fibers are opened and then placed in a cotton blending machine for blending; S2: The blended fibers are combed into a fiber web in a carding machine, and then the fiber web is put into a needle punching machine for needle punching, so that the thickness of the fiber reinforcement layer is 0.12 mm.

[0046] Preparation Example 2.4 The fiber reinforced layer differs from Preparation Example 2.1 in that no carbon fiber is added, and the carbon fiber in the raw material is replaced with polylactic acid fiber of equal quality, and the other steps are the same as Preparation Example 2.1. Example

[0047] Example 1 An environmentally friendly basketball leather, comprising a base fabric layer, a composite PU surface layer and a surface finishing layer laminated in sequence, wherein the composite PU surface layer comprises a first PU surface layer, a fiber reinforcement layer and a second PU surface layer laminated in sequence, and a side of the first PU surface layer facing away from the fiber reinforcement layer is laminated to the base fabric layer; The raw materials and their amounts are shown in Table 2, and the thickness values ​​of each layer are shown in Table 3, wherein the base fabric layer is made of polylactic acid non-woven fabric, the modified thermally expandable microspheres are obtained by Preparation Example 1.1, and the fiber reinforcement layer is obtained by Preparation Example 2.1.

[0048] Table 2 Table 3 The method for preparing the environmentally friendly basketball leather comprises the following steps: S1: mixing thermoplastic polyurethane, thickener, first leveling agent, first crosslinking agent and foam stabilizer to prepare slurry A; mixing first waterborne polyurethane, modified thermal expansion microspheres, second leveling agent, second crosslinking agent and defoamer to prepare slurry B; S2: Slurry A is coated on the base fabric layer to prepare a first PU surface layer, and then the fiber reinforcement layer is placed on the side of the slurry A coating layer away from the base fabric layer, and then rolled and dried to form a semi-cured base fabric A; S3: coating the slurry B on the side of the fiber reinforcement layer away from the base fabric layer in the semi-cured base layer A to prepare a second PU surface layer, and drying to obtain the semi-cured base fabric B; S4: embossing the semi-cured base fabric B; S5: a second aqueous polyurethane, rosin resin and butanone are mixed to prepare a surface coating liquid, which is applied to one side of the printed surface of the semi-cured base fabric B to prepare a surface coating layer, which is then dried.

[0049] Embodiment 2-4 An environmentally friendly basketball leather is different from Example 1 in that the raw materials and amounts are as shown in Table 2, the thickness of each layer is as shown in Table 3, and the other steps are the same as Example 1.

[0050] Example 5 An environmentally friendly basketball leather, which differs from Example 1 in that the modified heat-expandable microspheres are prepared by Preparation Example 1.2, and the other steps are the same as those of Example 1.

[0051] Example 6 An environmentally friendly basketball leather, which differs from Example 1 in that the modified heat-expandable microspheres are prepared by Preparation Example 1.3, and the other steps are the same as Example 1.

[0052] Example 7 An environmentally friendly basketball leather, which differs from Example 1 in that the modified heat-expandable microspheres are prepared by Preparation Example 1.4, and the other steps are the same as those of Example 1.

[0053] Example 8 An environmentally friendly basketball leather, which differs from Example 1 in that the modified heat-expandable microspheres are prepared by Preparation Example 1.5, and the other steps are the same as those of Example 1.

[0054] Example 9 An environmentally friendly basketball leather, which differs from Example 1 in that the fiber reinforcement layer is prepared by Preparation Example 2.2, and the other steps are the same as Example 1.

[0055] Example 10 An environmentally friendly basketball leather, which differs from Example 1 in that the fiber reinforcement layer is prepared by Preparation Example 2.3, and the other steps are the same as Example 1.

[0056] Embodiment 11 An environmentally friendly basketball leather, which differs from Example 1 in that the fiber reinforcement layer is prepared by Preparation Example 2.4, and the other steps are the same as Example 1.

[0057] Comparative Example Comparative Example 1 An environmentally friendly basketball leather, which differs from Example 1 in that no heat-expandable microspheres are added, the heat-expandable microspheres in the raw material are replaced by an equal mass of the first water-based polyurethane, and the other steps are the same as those in Example 1.

[0058] Comparative Example 2 An environmentally friendly basketball leather, which is different from Example 1 in that the composite PU surface layer only includes a first PU surface layer and a second PU surface layer. The preparation method of the environmentally friendly basketball leather comprises the following steps: The method for preparing the environmentally friendly basketball leather comprises the following steps: S1: mixing thermoplastic polyurethane, thickener, first leveling agent, first crosslinking agent and foam stabilizer to prepare slurry A, then coating slurry A on base fabric layer to prepare first PU surface layer, and drying to form semi-cured base fabric A; S2: The first waterborne polyurethane, the modified thermal expansion microspheres, the second leveling agent, the second crosslinking agent and the defoaming agent are mixed to form a slurry B, and then the slurry B is coated on the side of the semi-cured base layer A away from the base fabric layer to prepare a second PU surface layer, and the semi-cured base fabric B is obtained after drying; S3: embossing the semi-cured base fabric B; S4: a second aqueous polyurethane, rosin resin and butanone are mixed to prepare a surface coating liquid, which is applied to one side of the printed surface of the semi-cured base fabric B to prepare a surface coating layer, which is then dried.

[0059] Performance testing The hand feel elasticity, wear resistance and impact resistance of Examples 1-11 and Comparative Examples 1-2 were tested using the following test methods and standards: 1. Hand feel and elasticity test: Touch the environmentally friendly basketball leathers prepared in No. 14, 1-11 and Comparative Examples 1-2 respectively, and judge the surface feel and elasticity; Feel level: soft, medium-soft, medium-hard; Elasticity level: good resilience, average resilience, poor resilience; 2. Abrasion resistance test: The basketball leather products prepared in Examples 1-11 and Comparative Examples 1-2 were tested according to the test method in QB / T 2726-2005 "Determination of abrasion resistance of leather in physical and mechanical tests", and the CS-10 grinding wheel was used in the test. The test conditions were a load of 1000 g and a test rotation number of 1500 rpm, and the surface state of each group of basketball leather was observed; Evaluation criteria: Level 1 is very obvious, Level 2 is relatively obvious, Level 3 is distinguishable, Level 4 is difficult to distinguish, and Level 5 is indistinguishable; 3. Impact resistance test: Referring to GB / T 14625.3-2008 "Basketball, football, volleyball, handball test methods Part 3: Dynamic impact resistance test method", the environmentally friendly basketball leathers obtained in Examples 1-11 and Comparative Examples 1-2 were subjected to impact resistance tests, and the number of impacts when damage occurred on the surfaces of different basketball leathers was recorded, and the experimental results were recorded in Table 4.

[0060] Table 4 According to the performance test results in Table 4, it can be seen that an environmentally friendly basketball leather of the present application can still maintain an intact surface state after a load of 1000g and a test rotation number of 1500 revolutions, without obvious surface wear and damage, and can still maintain a good surface state without surface damage after 20,000 impacts. This shows that the basketball leather of the present application not only has environmentally friendly raw materials and conforms to the concept of sustainable development, but also has excellent wear resistance and impact resistance, is soft to the touch, has good resilience, and has a good service life and sports safety.

[0061] According to the performance test results of Examples 1-8 and Comparative Example 1, it can be seen that the addition of modified heat-expandable microspheres and their unique shell-sheath structure enable the basketball leather to show better resistance to deformation when facing impact and wear, thereby absorbing and dispersing part of the impact capacity, playing an effective shock-absorbing effect, and effectively reducing the impact of impact force and friction on the basketball leather, significantly improving the wear resistance and impact resistance of the basketball leather, and at the same time being able to improve the resilience of the basketball leather, so that it has more excellent performance.

[0062] Carbon nanopowder has high mechanical strength and wear resistance. The modified thermally expandable microspheres prepared as raw materials can form a more complex energy absorption and dissipation system. When the basketball leather is hit, the carbon nanopowder in the microspheres can absorb and disperse part of the impact energy, and at the same time synergize with the expansion process of the microspheres to further reduce the stress level of the basketball leather and improve the wear resistance and impact resistance of the basketball leather.

[0063] According to the performance test results of Examples 1-4, Examples 9-11 and Comparative Example 2, it can be seen that the sandwich-structured composite PU surface layer formed by sequentially bonding the first PU surface layer, the fiber reinforcement layer and the second PU surface layer, on the one hand, forms a more solid and supporting matrix, which can effectively improve the overall supporting strength of the basketball leather base fabric layer, and enhance the wear resistance and impact resistance of the basketball leather; on the other hand, the non-woven fabric formed by fiber needle punching has a three-dimensional network structure, and its linear density is much lower than that of ordinary synthetic leather, which makes the prepared basketball leather softer, more folding resistant and more resilient, and provides a feel closer to natural leather.

[0064] Carbon fiber has good wear resistance, high strength and modulus. As one of the base materials of the fiber-reinforced layer, it improves the durability of the fiber-reinforced layer and makes a significant contribution to the improvement of the wear resistance and impact resistance of basketball leather. At the same time, the fiber-reinforced layer prepared with carbon fiber has excellent shock-absorbing properties, which makes the basketball leather have better resilience and promotes the overall stability of the basketball leather.

[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An environmentally friendly basketball leather, characterized in that: It comprises a base fabric layer, a composite PU surface layer and a surface finishing layer which are laminated in sequence, wherein the composite PU surface layer comprises a first PU surface layer, a fiber reinforcement layer and a second PU surface layer which are laminated in sequence, and the first PU surface layer is laminated to the base fabric layer on a side away from the fiber reinforcement layer; In parts by weight, the raw materials of the first PU surface layer include 15-25 parts of thermoplastic polyurethane, 0.2-0.5 parts of thickener, 0.01-0.05 parts of first leveling agent, 0.5-1 parts of first cross-linking agent and 0.5-1 parts of foam stabilizer; The raw materials of the second PU surface layer include 30-45 parts of the first waterborne polyurethane, 3-7 parts of modified thermal expansion microspheres, 0.1-0.5 parts of the second leveling agent, 1.2-1.5 parts of the second cross-linking agent and 0.1-0.3 parts of the defoaming agent.

2. The environmentally friendly basketball leather according to claim 1, characterized in that: In parts by weight, the raw materials of the modified heat-expandable microspheres include 15-25 parts of cyano-containing olefin monomers, 5-10 parts of double-bond-containing ester monomers, 2-7 parts of carbon nanopowder, 0.2-0.8 parts of initiators and 5-10 parts of low-boiling-point alkanes, and also include 1-1.5 parts of sodium dodecyl sulfate, 0.1-0.3 parts of polyvinyl pyrrolidone, 0.1-0.3 parts of sodium nitrite and 10-15 parts of sodium chloride.

3. The environmentally friendly basketball leather according to claim 2, characterized in that: The cyano-containing olefin monomer is selected from any one of acrylonitrile or crotononitrile; the double-bond-containing ester monomer is methyl methacrylate, butyl acrylate and vinyl acetate in a mass ratio of 1:(2-6):(1-5); the initiator is azobisisobutyronitrile; and the low-boiling-point alkane is selected from any one of isopentane or n-octane.

4. The environmentally friendly basketball leather according to claim 2, characterized in that: The preparation method of the modified heat-expandable microspheres comprises the following steps: Sodium lauryl sulfate, polyvinyl alcohol, sodium nitrite and sodium chloride are mixed and added into deionized water at a solid-liquid ratio of 1:(9-11) to form an aqueous phase; The cyano-containing olefin monomer, the double-bond-containing ester monomer, the carbon nanopowder, azobisisobutyronitrile and the low-boiling-point alkane are mixed and stirred uniformly to obtain an oil phase; The oil phase is added to the water phase, stirred at a speed of 8000-9000 rpm for 3-5 minutes to disperse, and then pressurized under a nitrogen atmosphere, reacted at 50-80° C. for 18-20 hours, then reduced in pressure, cooled to room temperature, centrifuged, dried, and sieved to obtain the product.

5. The environmentally friendly basketball leather according to claim 1, characterized in that: The fiber reinforcement layer includes nylon, polylactic acid fiber and carbon fiber in a mass ratio of (5-7):(2-4):(1-3).

6. The environmentally friendly basketball leather according to claim 1, characterized in that: In parts by weight, the raw materials of the surface coating layer include 5-10 parts of the second waterborne polyurethane, 5-10 parts of rosin resin and 20-30 parts of butanone.

7. The environmentally friendly basketball leather according to claim 1, characterized in that: The base fabric layer is made of polylactic acid non-woven fabric.

8. The environmentally friendly basketball leather according to claim 1, characterized in that: The thickness of the first PU surface layer is 0.26-0.3 mm, the thickness of the fiber reinforcement layer is 0.1-0.13 mm, and the thickness of the second PU surface layer is 0.42-0.47 mm.

9. The method for preparing an environmentally friendly basketball leather according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: mixing corresponding masses of thermoplastic polyurethane, thickener, first leveling agent, first crosslinking agent and foam stabilizer to prepare slurry A; mixing corresponding masses of first waterborne polyurethane, modified thermal expansion microspheres, second leveling agent, second crosslinking agent and defoamer to prepare slurry B; S2: Slurry A is coated on the base fabric layer to prepare a first PU surface layer, and then the fiber reinforcement layer is placed on the side of the slurry A coating layer away from the base fabric layer, and then rolled and dried to form a semi-cured base fabric A; S3: coating the slurry B on the side of the fiber reinforcement layer away from the base fabric layer in the semi-cured base layer A to prepare a second PU surface layer, and drying to obtain the semi-cured base fabric B; S4: embossing the semi-cured base fabric B; S5: The second water-based polyurethane, rosin resin and butanone are mixed according to mass to prepare a surface coating liquid, which is applied to one side of the printed surface of the semi-cured base fabric B to prepare a surface coating layer, which is then dried.

10. The method for preparing the environmentally friendly basketball leather according to claim 9, characterized in that: The method for preparing the fiber reinforced layer comprises the following steps: Nylon, polylactic acid fiber and carbon fiber are cut into short fibers respectively and then mixed evenly, opened and blended with cotton; the blended fibers are combed into a fiber web and then needle-punched to obtain the fiber web.